Quality of life and sexuality in women with lichen sclerosus: a cross‐sectional study. (1st February 2022) - Vittrup, G.; Mørup, L.; Heilesen, T.; Jensen, D.; Westmark, S.; Melgaard, D.
Summary: Background Lichen sclerosus (LS) affects the female anogenital area, causing anatomical changes. Reported symptoms include itching, soreness and dyspareunia. Aim To evaluate the quality of life and sexual functioning in women with LS. Methods In total, 158 women aged over 18 years, diagnosed with LS, and referred to North Denmark Regional Hospital from January 2018 to November 2019, were included. Three questionnaires, the Female Sexual Function Index (FSFI), Dermatology Life Quality Index (DLQI) and the World Health Organization Five‐Item Well‐Being Index (WHO‐5), were completed. Results The women (mean age 47 years, range 18–76) presented a low score on all FSFI scales, with a mean score of 13.83 (95% CI 12.46–15.20), indicating reduced sexual functioning. The subgroup evaluation scored for desire 2.32, arousal 2.23, lubrication 2.39, orgasm 2.28, satisfaction 3.02 and pain 1.59. The DLQI results revealed a mean score of 7.88 (95% CI 7.02–8.74), indicating a moderate effect on the women's everyday life. The mean subscores were treatment 0.32, sexual difficulties 1.56, relations 1.02, work/study 0.34, sport 0.45, social activities 0.54, clothing 0.89, shopping 0.22, embarrassment 0.99 and itching, soreness and pain 1.55. The mean score for the WHO‐5 was 56.66 (95% CI 53.48–59.84) indicating that 40% of the women had signs of depression. Conclusion LS has a considerable influence on the sexual functioning and quality of life of women. Healthcare professionals must not only consider the biological aspects but also the psychological and social aspects. Abstract : This study documents and confirms that women with lichen sclerosus (LS) have a high prevalence of sexual difficulties. Women with LS experience moderate effect on their general quality of life, and 40% of women with LS experience signs of depression.